APPLICATION OF HOME LIGHT CONTROL SYSTEM USING ARDUINO WITH MOBILE BASED WIFI MEDIA - Uning Lestari; Erfanti Fatkhiyah; Andung Febi Prakoso (IJISCS (International Journal of Information System and Computer Science), 2018)
Nowadays, technology development encourage people to think creatively, not not only to explore new discoveries, but also to maximize existing technological performance to ease human work in everyday life. The need for an automatic control system is needed with the increasing activity of each individual community with various erratic activities and times. As a result, many activities in the household are delayed, such as turning on or turning off the lights in every room at night and in the morning. Smart home system is one solution that suits the needs of the current automatic controllers. Smart home system is a home or building is equipped with an integrated technology with the help of the tool/tools which can be a computer or other device, for example a smartphone to provide all the comfort, safety, security and energy saving is automatic and programmed. The smart home system can be used to control almost all equipment and equipment at home, from lighting settings to various household appliances, which can be done only by using sound, infrared light or remote control. In this study, a smart home system was created for home light control system applications using Arduino Uno microcontroller via mobile-based wifi media. With this application the user can control the home lights by turning off or turning on the home lights remotely through the mobile media. Thus the efficiency of electricity use becomes more maintained.